A molecular electron density theory study of hydrogen bond catalysed polar Diels–Alder reactions of α,β-unsaturated carbonyl compounds - Luis R. Domingo; Patricia Pérez; Mar Ríos-Gutiérrez; M. José Aurell (Tetrahedron Chem, 2024)
The hydrogen bond (HB) catalysed Diels-Alder (DA) reactions of acrolein with cyclopentadiene have been investigated within the Molecular Electron Density Theory (MEDT) at the ωB97X-D/6-311G(d,p) computational level. The formation of HBs increases the electrophilicity of these species, suggesting an acceleration of these polar Diels-Alder (P-DA) reactions with forward electron density flux. Formation of one or two HBs with acrolein decreases the activation energies of the HB-catalysed P-DA reactions by 1.7 (methanol) and 4.0 (squaramide) kcal·mol−1, with the corresponding DA reactions exhibiting low endo stereoselectivity. These HB-catalysed DA reactions proceed through non-concerted one-step mechanisms via asynchronous transition state structures (TSs). An Interacting Quantum Atoms (IQA) energy partitioning analysis of the TSs indicates that the intra-atomic stabilization of the acrolein framework, coupled with the increase of the global electron density transfer, plays a crucial role in reducing the activation energies of these HB-catalysed DA reactions.